A arbitragem comercial e os Impactos da coisa julgada - Costa, Juliana Ruiz (2023)
This thesis aims to analyze the impact of res judicata on Commercial Arbitration, examining both the effect that the res judicata of arbitral awards has on the entire legal system and the impact of res judicata arising from judicial decisions on Arbitration. A comprehensive analysis will be conducted on how the arbitral system deals with the issue of res judicata and how it is formed in this specific context. Arbitration is an essential method of dispute resolution, both in Brazil and internationally. On the other hand, the study of res judicata is considered one of the classical topics of Law, as it is intrinsically related to the legal certainty of the parties. However, although res judicata is a highly discussed topic in civil procedure, the study of res judicata in Arbitration remains largely unexplored. With the development of arbitration practice, new questions and unforeseen developments arise in the theoretical treatment given to it. Equally, despite the classical nature of the study of res judicata, it constantly assumes new contours and gains new complexities. Thus, this thesis seeks to explore the relationship and ramifications of these two institutes (Arbitration and res judicata) and draw some conclusions about the impact of res judicata generated by arbitral awards on judicial proceedings and vice versa. The thesis also examines the topic of the enforcement of foreign arbitral awards, especially the regulation that res judicata receives in the international scenario, and the impact of res judicata arising from foreign arbitral awards when they are included into the Brazilian Legal System